2010
DOI: 10.1007/s00018-010-0393-8
|View full text |Cite
|
Sign up to set email alerts
|

Myoinhibiting peptides are the ancestral ligands of the promiscuous Drosophila sex peptide receptor

Abstract: Male insects change behaviors of female partners by co-transferring accessory gland proteins (Acps) like sex peptide (SP), with their sperm. The Drosophila sex peptide receptor (SPR) is a G protein-coupled receptor expressed in the female's nervous system and genital tract. While most Acps show a fast rate of evolution, SPRs are highly conserved in insects. We report activation of SPRs by evolutionary conserved myoinhibiting peptides (MIPs). Structural determinants in SP and MIPs responsible for this dual rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 58 publications
0
109
0
Order By: Relevance
“…Despite the highly specific behavioural response, however, SPR is broadly expressed in the nervous system and the oviduct. SPR also binds myoinhibitory peptides (MIPs) with high affinity, which do not induce the SP-mediated postmating switch [17][18][19]. It therefore appears that SPR has additional functions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the highly specific behavioural response, however, SPR is broadly expressed in the nervous system and the oviduct. SPR also binds myoinhibitory peptides (MIPs) with high affinity, which do not induce the SP-mediated postmating switch [17][18][19]. It therefore appears that SPR has additional functions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that SPR expression in a limited number of pickpocket-expressing neurons in the female common oviduct was sufficient to rescue the mutant phenotype, suggesting that these neurons are targeted by SP (Yang et al 2009;Hanin et al 2012). Interestingly, neuronally expressed SP reduced receptivity and increased oviposition in the absence of SPR, suggesting an additional pathway capable of inducing PMR (Haussmann et al 2013).Several studies have shown that myoinhibitory peptides (MIPs) are also potent ligands for SPR (Kim et al 2010;Poels et al 2010;Yamanaka et al 2010 Here, we developed a GFP-tagged SP (G-SP) derived from D. melanogaster and used it to visualize cross-species binding activity to female reproductive system of 11 species. G-SP binds to the oviducts of six species belonging to the D. melanogaster species group, but not to those outside the group.…”
mentioning
confidence: 99%
“…Several studies have shown that myoinhibitory peptides (MIPs) are also potent ligands for SPR (Kim et al 2010;Poels et al 2010;Yamanaka et al 2010 Here, we developed a GFP-tagged SP (G-SP) derived from D. melanogaster and used it to visualize cross-species binding activity to female reproductive system of 11 species. G-SP binds to the oviducts of six species belonging to the D. melanogaster species group, but not to those outside the group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MIP neuropeptides are characterized by a W-X 6-8 -Wamide motif (11). In Platynereis, the last but not the first tryptophan (W) residue is crucial for MIP receptor activation and hence induction of larval settlement.…”
mentioning
confidence: 99%